Overturning and Reinforcement of Single-Column Pier Curved Girder Bridge Considering the Secondary Effect of Overturning - Xinglian Huang; Lan Chen; Yang Quan; Xinfeng Yin (Buildings)
The overturning resistance of curved single-column pier bridges has garnered increasing attention with the rise in infrastructure demands. However, aspects such as the secondary effects of overturning and the dynamic interactions between vehicles and bridges have not been fully explored. Hence, a refined finite element model incorporating Vehicle–Bridge Interaction (VBI) dynamics has been applied to a highway ramp bridge in this study, aiming to elucidate how VBI-induced vibrations contribute to bridge overturning and to develop effective reinforcement strategies for enhanced stability under eccentric loads. The analysis suggests that the rotation of the main girder, influenced by eccentric overload, is a significant factor in the overturning process. The initial overturning stability coefficient was found to be 0.948, pointing to potential areas for improvement. By implementing targeted reinforcement measures, specifically the addition of cover beams, the stability coefficient was improved to 2.626. The study provides insights into VBI-induced overturning in curved single-column pier bridges, offering a reinforcement strategy aimed at enhancing stability under eccentric loads.